Reducing Key Barriers to Classroom Physical Activity Improves Implementation Fidelity in Ontario Elementary Classrooms - Hannah Bigelow; Shelby Singh; Barbara Fenesi (MDPI AG, 2023)
Background: Schools are the front lines of children's physical activity. Students who participate in daily physical activity (DPA) within their classrooms show improved physical strength, physical fitness, academic success, and mental well-being. However, teachers face many barriers to DPA implementation. The current study evaluated whether providing a DPA toolkit that offers greater access to DPA resources and requires minimal training for teachers to implement could improve DPA implementation. Methods: A total of 343 teachers from Ontario, Canada, completed a pre-survey assessing DPA practices and were given access to a DPA toolkit containing easily accessible and usable DPA resources to implement between January and March 2023. A total of 142 participants completed the post-survey to assess for changes in DPA practice. Several repeated measures of ANOVA were conducted with a three-level factor of grade level (1-3, 4-6, and 7-8) and within the subject factor of time (pre- to post-survey) on key outcome variables. Results: Findings revealed that the DPA toolkit improved DPA fidelity (p = 0.007, η2p = 0.053) and promoted teacher confidence in implementing DPA (p < 0.001, η2p = 0.285) and enjoyment in implementing DPA (p < 0.001, η2p = 0.177). Many improvements were most prominent among teachers teaching grades 1-3 and 4-6. Conclusions: By providing teachers with adequate DPA resources that minimize teacher training, there can be significant improvements in DPA implementation with notable cognitive and psycho-emotional benefits for both teachers and students.